RB1CC1 duplication and aberrant overexpression in a patient with schizophrenia: further phenotype delineation and proposal of a pathogenetic mechanism - Edoardo Errichiello; Roberto Giorda; Antonella Gambale; Achille Iolascon; Orsetta Zuffardi; Sabrina Giglio (Molecular Genetics & Genomic Medicine, 2021)
Abstract Background Copy number variants in coding and noncoding genomic regions have been implicated as risk factor for schizophrenia (SCZ). Rare duplications of the RB1CC1 gene were found enriched in SCZ patients. Considering that the effect of such duplications on RB1CC1 expression has never been evaluated and partial gene duplications of RB1CC1 have also been reported in SCZ patients, it is unclear whether the pathogenesis is mediated by haploinsufficiency rather than genuine overexpression of the gene. Methods and Results We studied a patient with schizophrenia, suicidality, and obesity, who carried a de novo RB1CC1 complete duplication, as assessed by high‐resolution array‐CGH. Molecular breakpoint cloning allowed to identify nonhomologous end joining (NHEJ) as driving mechanism in this rearrangement. On the contrary, trio‐based whole‐exome sequencing excluded other potential causative variants related to the phenotype. Functional assays showed significant overexpression of RB1CC1 in the peripheral blood lymphocytes of the proband compared to control subjects, suggesting overdosage as leading mechanism in SCZ pathophysiology. Conclusion We hypothesized a pathogenetic model that might explain the correlation between RB1CC1 overexpression and schizophrenia by altering different cell signaling pathways, including autophagy, a promising therapeutic target for schizophrenic patients.